Reviews (New blackfriars, 1966)
OLD TESTAMENT THEOLOGY (Volume Two): The Theology of Israel's Prophetic Traditions by Gerhard Von Rad. Translated by D. M. G. Stalker The Acts of the Apostles 1–13. Translators John W. Fraser and W. J. G. McDonald. Editors David W. Torrance and Thomas F. Torrance The Epistles of Paul The Apostle to the Galatians. Ephesians. Philippians and Colossians. Translator T. H. L. PARKER. Editors David W. Torrance and Thomas F. Torrance L'EGLISE NE S'EST PAS TUE. Dossier hongrois 1940-1945, by Jeno Levai LIGHT ON THE NATURAL LAW edited and introduced by Illtud Evans, O.P. THE FUTURE OF CATHOLIC CHRISTIANITY. Ed. Michael de la Bedoyere THE MIND OF DANTE. Ed. U. Limentani PRE-REFORMATION ENGLISH SPIRITUALITY. Edited and introduced by James Walsh. S.J. Burns and Oates SIMONE WEIL. A SKETCH FOR A PORTRAIT, by Richerd Rees THE STOLEN DESERT: A STUDY OF UHURU IN NORTH EAST AFRICA, by The Earl of Lytton